The doctor-patient non-relationship: from closing to maximum availability. - Zanetti, Michela; Lalli, Anna (Rivista di Psicologia Clinica, 2013)
In this study, we present a field research on function of the clinical psychologist within the hospital activity in departments with a high mortality rate. Starting from the demand for counseling of clients (doctors and managers of operational units) to the Psychology Service Hospital, through the analysis of clues very different: the spaces, the words of patients, doctors and nurses, we arrived at putting a construction on the affective symbolization of contexts . The criterion which bases the doctor-patient relationship is assumed to be due to the fear of death that guides health professionals within two distinct relational models: the unavailability and high availability regardless.